The Impact of Reward Satisfaction on Nurses' Career Development in the Inpatient Ward of Gambiran Hospital Kediri - Alfian Fawzi; Faisal Rahman; Aprin Rusmawati (Journal Of Nursing Practice, 2025)
Background: Career self-efficacy is a person's perception of their ability to choose and develop optimally in a particular field of work. Reward such as bonuses, promotions, or recognition of achievements, aims to provide incentives to employees to work better to achieve success in their careers. Purpose: This study aims to analyze the association between reward satisfaction and the career self-efficacy of nurses working in the inpatient ward at Gambiran  Hospital, Kediri City. Methods: A quantitative associative research design was applied using proportionate stratified sampling. A total of 82 respondents participated in the study. Data were collected through questionnaires and analyzed using ordinal regression. Results: Ordinal regression analysis revealed a significant relationship between reward satisfaction and nurses' self-efficacy in advancing their career paths, with a p-value of 0.029 (p < 0.05). Reward satisfaction accounted for 45.8% of the variation in self-efficacy. Conclusion: Reward satisfaction significantly influences nurses' self-efficacy in advancing their career paths. These findings can serve as a reference for hospitals to enhance human resource management strategies.